The extent of knowledge and awareness of Saudi university students about green finance: An exploratory study of a sample of female students at Taif University - Felimban, Razaz Houssien (Journal of Economic, Administrative and Legal Sciences, 2025)
Sustainable finance is an essential and fundamental component of achieving development. It is a goal that all organizations aspire for, and it is the most urgent topic in accommodating current generations. Sustainability in this context means the importance of not harming the environment or depleting natural resources, which supports long-term environmental and social cooperation. Therefore, the current study aims to identify the extent of awareness and knowledge of Taif University students about green finance during the academic year 1445 AH. To achieve these goals, the study relied on the descriptive analytical approach and the social survey method, in addition to using the questionnaire as a data scanning tool from the pictorial drawing. This study was conducted on a sample of (334) female students from College of Business Administration in Taif University. After collecting the data, the researcher utilized the Statistical Package for Social Sciences (SPSS) to analyze the data. The results of the study came to what is worn from the level of creativity among students in green finance in terms of (the concept of green, its judiciary, its products, and its different aspects). Among the most important elements included are the topics of green sustainability financing and complete curricula, as much as students target events and seminars to benefit from green resources in the environment and the economy. And expect them to act as  an active part in achieving the vision of 2030.
Keywords: knowledge; awareness; green finance; Taif University; KSA